The urological anomalies associated with anorectal malformations - Shatha A. Hmed Al-kawaz; Maha A. Lattuf Al-Rudaini; Thura K. Jaafer (مجلة كلية الطب, 2013)
Background: Urological anomalies are frequently associated with anorectal malformations which are a common source of significant morbidity.